Gestão de satisfação e fidelidade do cliente: um estudo dos fatores que afetam a satisfação e fidelidade dos compradores de automóveis - Pinheiro, Isabel Nobre (2003)
This Master s thesis presents a discussion on customer satisfaction models investigating the relations of antecedent variables service quality, price index, complaint handling, image, affective and calculative commitment, with satisfaction and loyalty. The scope of the research is the influence of service dimensions in the car buyer s satisfaction and loyalty. A sample of 91 customers was surveyed among new cars buyers of one brand in Natal city, Brazil, and the data was analyzed using multiple regression analysis. The literature review covers subjects such as customer satisfaction, management system, customer satisfaction measurement index models. The main findings suggest that satisfaction with the car brand is mainly influenced by customization of the service, time for accomplishing servicing, and the way the dealer handle complains. Regarding the dealer itself the main variable related to satisfaction is also time for accomplishing servicing. Considering customer loyalty, the customer satisfaction with the dealer explain strongly the loyalty with the brand/manufacturer. Also, the satisfaction, affective commitment and complains handling were found related to loyalty, as the stronger variables explaining the loyalty variance. One main conclusion is that service provided by dealers is one key factor influencing the customer satisfaction and loyalty in auto industry